The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3171/2020.2.jns193221
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a risk scoring model for postoperative adult moyamoya disease

Abstract: OBJECTIVEThe current grading system for moyamoya disease (MMD) is focused on angiographic studies with limited clinical application. The authors aimed to determine relevant factors that may impact postoperative outcome and establish a scoring system to predict the functional outcome.METHODSAdult patients with MMD who underwent treatment between 1998 and 2016 were included. Factors such as age, sex, comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…31 Other risk factors include higher mRS scores at admission, advanced Suzuki stages, and PCA involvement. 4,6 It has been reported that steno-occlusion in PCA is a hallmark of MMD progression and is significantly associated with an increased risk of recurrent ischemic stroke. 7,32 It remains true after we extend follow-up that PCA involvement accounted for the greatest discriminant weight in model 1 but is less significant than functional connectivity in model 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Other risk factors include higher mRS scores at admission, advanced Suzuki stages, and PCA involvement. 4,6 It has been reported that steno-occlusion in PCA is a hallmark of MMD progression and is significantly associated with an increased risk of recurrent ischemic stroke. 7,32 It remains true after we extend follow-up that PCA involvement accounted for the greatest discriminant weight in model 1 but is less significant than functional connectivity in model 2.…”
Section: Discussionmentioning
confidence: 99%
“…5 We included BMI in the prediction model because smoking, hyperlipidemia, hypertension, and diabetes are prevalent comorbidities and contribute to poor outcomes in patients with MMD. 6,20,21 These comorbidities are strongly correlated with BMI. 31 Other risk factors include higher mRS scores at admission, advanced Suzuki stages, and PCA involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moyamoya disease, a rare and incurable disease, is a primary cause of strokes or transient ischemic attacks in adolescents 1 . The prevalence of moyamoya disease is reported to be 3.16 per 100,000 people, and the incidence rate is reported to be 0.5 per 100,000 people per year 2 . The highest incidence rates are among people aged 5–15 and 30–49 years.…”
Section: Introductionmentioning
confidence: 99%
“…Moyamoya disease can easily cause cerebral vascular hypo circulation-related symptoms even with minor changes in blood flow. It can also cause transient cerebral ischemic attacks in stressful situations 7 ; therefore, stress management is required 2 , 8 . The health issues and symptoms experienced by adolescents with moyamoya disease are often stress-related 9 .…”
Section: Introductionmentioning
confidence: 99%